The Intermarriage Life Satisfaction Premium - Potarca, Gina; Bernardi, Laura (Journal of happiness studies, 2021)
Research on the consequences of intermarriage is almost exclusively looking at immigrants’ labour market outcomes, with little attention given to non-economic indicators. Drawing from set-point theory and taking on a dynamic approach, the authors examine whether having a different- versus a same-origin partner is subject to a selection on life satisfaction, or associated with a greater short-term improvement in migrants and natives’ subjective well-being (SWB). The paper also aims to investigate whether gains from exogamy diminish at a faster rate than those from endogamy, and whether intermarriage produces a long-term drop in SWB. Using data from the German Socio-Economic Panel and controlling for time-varying unobserved heterogeneity, we run a set of random- and fixed-effects models that uncover changes in life satisfaction before and after the transition into a mixed marriage. Results provide evidence of a selection on life satisfaction for exogamous first generation migrant men. Findings also show that with the exception of migrant men, there is an inter-partnering SWB gain, albeit insignificant, in the pre-marital cohabitation phase. Native women display an intermarriage premium when transitioning to marriage and shortly after, but also a significant SWB drop in later years. Overall, contrary to previous studies that did not account for unobserved characteristics, we show that in the long run, mixed marriages are not more detrimental to SWB than unions involving same-origin partners.